A perspectiva do controle da evasão discente a partir da identificação dos principais fatores: estudo de caso na Universidade Federal do Pampa - Rodrigues, Adriano Correia (2019)
The present study aims to identify the main factors related to the student evasion process in order to create subsidies to reduce dropout rates, a study directed to undergraduate courses at the Federal University of Pampa - Jaguarão campus. The literature review contributed to a better understanding of the evasion phenomenon and to the choice of the data collection instrument. The students evaded from (2015 to 2017) of the 5 face-to-face courses offered at the Jaguarão campus made up the sample. For the treatment and analysis of the research data, the SPSS Statistics version 20 system was used, applying the factorial analysis using the multivariate statistical method. The determinants of student evasion were distributed in the internal or external dimensions of the Institution, with three external factors: personal vocation, socioeconomic partner, socioeconomic environment; internal factors are pedagogical requirements and institutional motives. The five variables with the highest average on the likert scale are change of interest, choice of life and/or professional indecision; for not having met my expectations; discovery of new interests and entry/option for another course; pedagogy of inefficient teachers and a lack of association between theory and practice in the disciplines. The results of the research indicate a predominance of external circumstances. However, from the findings, twelve programs/actions aimed at reducing student dropout rates at the Jaguarão campus were listed.